A Case of Cervical Dystonia with Non Responsive To Usual Noninvasive Treatment (Journal of Shaheed Suhrawardy Medical College, 2017)
Cervical dystonia is a focal dystonia characterized by neck muscles contracting involuntarily-causing abnormal movement and awkward posture of the head and neck. A rare disorder can occur at any age even at infancy. Symptoms generally begin gradually and then reach a point where they don't get substantially worse. Asymmetry of the sternocleidomastoid (SCM) is often present in untreated patient. There is no cure for cervical dystonia. Injecting botulinum toxin into the affected muscles often reduces the signs and symptoms of cervical dystonia. In this case, it has been described a rare case of a forty seven year old male patient with a history of cervical dystonia presented with struggle with head position, resisting but never overcoming the tendency of his head to assume an unnatural position. The management including drugs like oral analgesic, muscle relaxant, anti-Parkinson drug & even antipsychotic drug were used. Physiatric approach like different modalities of heat such as Short wave diathermy (SWD), Microwave diathermy (MWD) & Ultra sound therapy (UST) were used. Brace like cervical collar and different type of exercise was also prescribed, even botulinum toxin injected into suspected muscles but all discussed above failed in this case.J Shaheed Suhrawardy Med Coll, June 2014, Vol.6(1); 44-46